Repeated lumbar punctures within 3 days may affect CSF biomarker levels - Repeated lumbar punctures within 3 days without sleep intervention - Olsson, Martin; Ärlig, Johan; Hedner, Jan; Blennow, Kaj; Zetterberg, Henrik (University of Gothenburg, 2019)
As an extension of a study on the relationship between sleep deprivation and cerebrospinal fluid (CSF) biomarkers for Alzheimer’s disease, we performed two Lumbar punctures (LPs) within three days in 13 healthy volunteers. Our aim was to investigate CSF biomarker dynamics in relation to sleep deprivation. An unexpected sharp rise in biomarker concentrations in the second sample made us consider an artifact and we therefore repeated the experiment, but without sleep restriction, in four additional individuals. A similar rise in biomarker levels were evident, suggesting an inherent methodological problem with repeated LPs.

Participants with controled normal sleep. Biomarker concentrations from each individual lumbar puncture.

En förlängning av en studie om förhållandet mellan sömnbrist och biomarkörer för Alzheimers sjukdom, i cerebrospinalvätska (CSF). Friska frivilliga (N=13) utsattes för upprepade lumbalpunktioner med tre dagars mellanrum. Vårt mål var att undersöka CSF-dynamik i förhållande till sömnbrist. En oväntad kraftig ökning av biomarkörkoncentrationerna i det andra provet fick oss att misstänka en artefakt och vi upprepade därför experimentet, men utan sömnbegränsning, i fyra ytterligare individer. Vi kunde då se en liknande ökning i biomarkörnivåer, vilket antyder ett inneboende metodproblem med upprepade lumbalpunktioner.

Försökspersoner som med kontrollerad normalsömn. Lumbalpunktion med 3 dagars mellanrum. Biomarkörkoncentrationer från varje enskild lumbalpunktion.
Upprepade lumbalpunktioner inom 3 dagar kan påverka biomarkörer i likvor - Upprepade lumbalpunktioner inom 3 dagar utan sömnintervention
Keywords: Cerebrospinal Fluid; Cerebrospinalvätska; Cerebrospinal Fluid Proteins; Likvorproteiner; Amyloid beta-Peptides; Amyloid beta-peptider; lumbar puncture; lumbalpunktion; tau; tau; cerebrospinal fluid proteins; proteiner i cerebrospinalvätska; CSF; CSF; Medical and Health Sciences; Medicin och hälsovetenskap